Short communication: decrease in mitochondrial transmembrane potential in peripheral blood mononuclear cells of HIV-uninfected subjects undergoing HIV postexposure prophylaxis - Groener, Jan B; Seybold, Ulrich; Vollbrecht, Thomas; Bogner, Johannes R (AIDS research and human retroviruses, 2011)
To monitor the mitochondrial transmembrane potential (ΔΨm), peripheral blood mononuclear cells (PBMCs) from 18 HIV-uninfected individuals completing a 4-week course of HIV postexposure prophylaxis (PEP) with emtricitabine/tenofovir and lopinavir/ritonavir were analyzed. ΔΨm was assessed by FACS analysis after staining with JC-1 using a mixed effects regression analysis. Apoptosis was determined by Annexin-V-FITC and propidium iodide staining. ΔΨm decreased significantly during HIV-PEP (p=0.0015 for the linear term, p=0.0039 for the quadratic term of days on PEP) and normalized several weeks after stopping antiretrovirals. The apoptosis rates did not change significantly (p=0.42). Even newer drugs such as tenofovir and emtricitabine may cause side effects due to mitochondrial dysfunction.